The Effect Of Laughter Therapy On Blood Pressure Of Elderly People With Hypertension In The Working Area Of Taba Lubuk Linggau Health Center - Utami, Try; Azissah, Danur; Pebriani, Emi (Journal of Multidisciplinary Research, 2025)
Increased blood pressure in the elderly generally occurs due to decreased organ function in the cardiovascular system. Hypertensive disease is still the highest non-communicable disease suffered by the elderly. Laughter Therapy is laughter that starts step by step. Laughing for 5-10 minutes can stimulate the release of endorphin and serotonin, which is a kind of natural morphine of the body and also melatonin. Laughter will increase blood flow and oxygen in the blood. Laughter therapy can help the healing process and reduce complaints experienced by clients. This study aims to determine the effect of laughter therapy on blood pressure in the elderly with hypertension in the Taba Lubuklinggau Health Center Working Area.The research method used a pre-experimental design with a one group pre-post test design type. Data were collected using observation sheets on 18 elderly respondents who experienced hypertension in the Taba Lubuk Linggau Health Center Working Area. The results of the univariate test analysis that most of the respondents 10 people (55.6%) were aged 50-60 years, Half of the respondents 9 people 50.0%) were male, Half of the respondents 9 people (50.0%) before laughing therapy had blood pressure in Stage II, Most of the respondents 11 people (61.1%) after laughing therapy in the elderly before and after giving laughing therapy obtained a significant change with a value of p = 0.000 (p <0.05). there is an effect of laughing therapy on blood pressure in the elderly with hypertension in the working area of Puskesmas Taba Lubuk Linggau.Researchers suggest to the Taba Lubuklinggau Health Center to be able to provide services and provide laughter therapy for hypertensive patients at the Taba Lubuklinggau Health Center to reduce the incidence of hypertension in the elderly.